Precision Improvement for the Detection of TGC via RBF Network - Yue Yan (Shock and Vibration)
The approach of multipoint measurement, with increasing hardware cost, should no longer be adopted against the problem of low detection precision on the quality and concentration measurement of large-caliber or irregular pipeline gas with the single platinum film probe. Alternatively, the data correction and improvement can be carried out through establishing an RBF model to detect sample gas after preprocessing. Furthermore, the computer simulation and error analysis can be implemented by taking actual SO2 data emitted by one medium-sized coal-fired power plant in China as a training sample. Hence, it can be shown that this approach on improvement and analysis of continuous monitoring of the systematic integrated error against the instrument correction and flue gas emission has feasibility, and the comprehensive average error is less than 0.6%.